2013
DOI: 10.1093/carcin/bgt407
|View full text |Cite
|
Sign up to set email alerts
|

FAT10, an ubiquitin-like protein, confers malignant properties in non-tumorigenic and tumorigenic cells

Abstract: FAT10 (HLA-F-adjacent transcript 10) is an ubiquitin-like modifier, which has been implicated in immune response and cancer development. In particular, the hypothesis of FAT10 as a mediator of tumorigenesis stems from its ability to associate with a spindle checkpoint protein Mad2 during mitosis and cause aneuploidy, a hallmark of cancer cells. Furthermore, FAT10 is overexpressed in several carcinomas types, including that of liver and colon. Nevertheless, direct evidence linking FAT10 to cell malignant transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 35 publications
2
47
0
Order By: Relevance
“…NF-B is a transcription factor with multiple target genes, so the question arises, which are the genes downstream of FAT10 and NF-B? The microarray expression analysis of FAT10 overexpressing NeHepLxHT and HCT116 cells by Gao et al (2014) revealed that the chemokine receptors CXCR4 and CXCR7 were highly up-regulated in FAT10 overexpressing NeHepLxHT cells, consistent with other data showing that NF-B is a transcription factor for both genes (Katoh and Katoh, 2010;Tarnowski et al, 2010). CXCR4 and −7 are both described to promote invasion and tumor growth in several cancer types (Gao et al, 2010;Heinrich et al, 2012;Liang et al, 2005;Zheng et al, 2010).…”
Section: What Are the Mechanisms Behind Fat10 Overexpression?supporting
confidence: 74%
“…NF-B is a transcription factor with multiple target genes, so the question arises, which are the genes downstream of FAT10 and NF-B? The microarray expression analysis of FAT10 overexpressing NeHepLxHT and HCT116 cells by Gao et al (2014) revealed that the chemokine receptors CXCR4 and CXCR7 were highly up-regulated in FAT10 overexpressing NeHepLxHT cells, consistent with other data showing that NF-B is a transcription factor for both genes (Katoh and Katoh, 2010;Tarnowski et al, 2010). CXCR4 and −7 are both described to promote invasion and tumor growth in several cancer types (Gao et al, 2010;Heinrich et al, 2012;Liang et al, 2005;Zheng et al, 2010).…”
Section: What Are the Mechanisms Behind Fat10 Overexpression?supporting
confidence: 74%
“…Gao and colleagues (34) reported that high FAT10 expression enhanced the invasive, migratory nature of the transformed cell line and HCT116 via the NF-kB-CXCR4/7 pathway. Another study found that FAT10 promoted the invasion of HCC cells via the Akt/ GSK3b pathway (14).…”
Section: Discussionmentioning
confidence: 99%
“…FAT10 expression is supposed to have proapoptotic functions (Liu et al, 1999;Raasi et al, 2001;Ross et al, 2006), an influence on chromosomal stability and cell cycle regulation (Liu et al, 1999;Ren et al, 2011), NF-kB signaling (Gong et al, 2010) and aggresome formation (Kalveram et al, 2008). In addition, FAT10 has been suggested to have antiapoptotic functions and is implicated in carcinogenesis because it is expressed in various cancer types (Gao et al, 2014;Lee et al, 2003;Lukasiak et al, 2008;Zhang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%